2007
DOI: 10.1002/pros.20675
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative, spatial resolution of the epigenetic field effect in prostate cancer

Abstract: This study quantifies previous observations of methylation in histologically negative samples and provides important assessment of field effects based on epigenetic events in cancer. These molecular approaches set the stage for consideration of such data in prospective trials for assessment of surgical margins and prediction of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
51
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 20 publications
10
51
0
1
Order By: Relevance
“…In contrast, few expression studies have reported molecular signatures and individual markers characteristic of prostatic TAHN tissues. Field cancerization is however evident at the genetic as well as the epigenetic level, as we have shown by altered telomeres in whole tissue TAHN extracts (11) and as shown by others by gene promoter methylation of APC, RARß2 and RASSF1A (34). Field cancerization in prostatic tissues is also evidenced by RNA/ protein expression analysis (35,36).…”
Section: Discussionsupporting
confidence: 60%
“…In contrast, few expression studies have reported molecular signatures and individual markers characteristic of prostatic TAHN tissues. Field cancerization is however evident at the genetic as well as the epigenetic level, as we have shown by altered telomeres in whole tissue TAHN extracts (11) and as shown by others by gene promoter methylation of APC, RARß2 and RASSF1A (34). Field cancerization in prostatic tissues is also evidenced by RNA/ protein expression analysis (35,36).…”
Section: Discussionsupporting
confidence: 60%
“…Although some of the above mentioned genes were already investigated in PCa, the results are sometimes contradictory [17,18] . Therefore, we analyzed tumor and tumor-adjacent tissues of a set of well-characterized prostatectomy specimens for a putative methylation field effect, which may be an indicator for PCa even in histologically tumor-free tissue.…”
mentioning
confidence: 99%
“…A number of investigators have confirmed the concept of precancerous molecular events in normal-appearing cells using different markers. [11][12][13] The obvious benefit of such field biomarkers is in the selection of men at high risk of cancer for close monitoring, while reassuring the low-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have confirmed field cancer effects in prostatic tissues. 12,15,16 Chemoprevention or early detection strategies would benefit from the profiling of cancer field biomarkers in high-risk populations. A histologically normal surgical margin may warrant molecular examination to preclude submicroscopic involvement.…”
Section: Discussionmentioning
confidence: 99%